Spatial and temporal variations in rocky intertidal communities - McQuaid, Christopher David (University of Cape Town, 2016)
Bibliography: pages 316-331. === This thesis attempts to give an understanding of intertidal conditions in the Cape Peninsula in terms of spatial and seasonal variations in rocky shore communities and falls into two distinct parts: 1. A general survey of intertidal conditions and an investigation of the interactions of certain physical factors on rocky shore communities. 2. An investigation of seasonal changes in the populations of certain abundant algae and gastropods at Dalebrook.